2015
DOI: 10.1126/science.1259114
|View full text |Cite
|
Sign up to set email alerts
|

An RNA polymerase III subunit determines sites of retrotransposon integration

Abstract: Mobile genetic elements are ubiquitous. Their integration site influences genome stability and gene expression. The Ty1 retrotransposon of the yeast Saccharomyces cerevisiae integrates upstream of RNA polymerase III (Pol III)-transcribed genes, yet the primary determinant of target specificity has remained elusive. Here we describe an interaction between Ty1 integrase and the AC40 subunit of Pol III and demonstrate that AC40 is the predominant determinant targeting Ty1 integration upstream of Pol III-transcrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
129
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(148 citation statements)
references
References 46 publications
18
129
0
Order By: Relevance
“…Because the cell lysis procedure disrupts the nuclear and cytoplasmic compartments, we do not think the lack of interaction is due to IN-NLS1ϩ2 being excluded from the nucleus, although we cannot entirely rule out this possibility. However, when combined with the Ty1-IN truncation analysis, our data suggest that the C-terminal 75 amino acids of Ty1-IN interact with RNA Pol III, which concurs with a recent studying showing a two-hybrid interaction between Rpc40 and Ty1-IN that was abrogated by removal of the C-terminal amino acids 578 -635 (24). Although BridierNahmias et al (24) found that Ty1-IN amino acids 578 -635 were also sufficient to interact with Rpc40 using a two-hybrid assay, we were unable to detect an interaction of a C-terminal Ty1-IN fragment (amino acids 422-636; IN-B) with Rpc82 or Rpc53 by co-IP (Fig.…”
Section: A-c)supporting
confidence: 91%
See 4 more Smart Citations
“…Because the cell lysis procedure disrupts the nuclear and cytoplasmic compartments, we do not think the lack of interaction is due to IN-NLS1ϩ2 being excluded from the nucleus, although we cannot entirely rule out this possibility. However, when combined with the Ty1-IN truncation analysis, our data suggest that the C-terminal 75 amino acids of Ty1-IN interact with RNA Pol III, which concurs with a recent studying showing a two-hybrid interaction between Rpc40 and Ty1-IN that was abrogated by removal of the C-terminal amino acids 578 -635 (24). Although BridierNahmias et al (24) found that Ty1-IN amino acids 578 -635 were also sufficient to interact with Rpc40 using a two-hybrid assay, we were unable to detect an interaction of a C-terminal Ty1-IN fragment (amino acids 422-636; IN-B) with Rpc82 or Rpc53 by co-IP (Fig.…”
Section: A-c)supporting
confidence: 91%
“…A standard 2-h comparative PCR analysis was performed using a 7500 Real Time PCR System (Applied Biosystems). The primers for the tLEU, tLEU de novo, and tGLY genes have been described (24). qPCR analysis was performed using the comparative C T method (⌬⌬C T method, Applied Biosystems) with TAF10 used as an internal control.…”
Section: Ty1-in-s In Vitro Bindingmentioning
confidence: 99%
See 3 more Smart Citations